Nonpharmacological treatment for individuals with intellectual disability and "personality disorder". Issue 4 (4th September 2018) - Williams, Emma M.; Rose, John
Abstract: Background: Research exploring nonpharmacological interventions for individuals with intellectual disability and personality disorder was reviewed. This should prove valuable to services and professionals contemplating how to offer interventions for these individuals. Method: A systematic search of electronic databases was conducted. Articles were considered for inclusion according to criteria based on the PICOS model. The quality of the research was assessed utilizing the evaluative method for determining evidence‐based practice. Results: Eleven studies were reviewed with quality assessment indicating that all provided weak research evidence. Consistent flaws included insufficient description of participants and lack of control groups. Conclusions: The research base exploring nonpharmacological interventions for individuals with intellectual disabilities and personality disorder includes many methodological flaws but reveals some useful information regarding the characteristics of these individuals and components of interventions to support them. Further research is needed to identify the differential effectiveness of interventions over and above other confounding factors.